Lightning NOx Emissions: Reconciling Measured and Modeled Estimates With Updated NOx Chemistry. Issue 18 (18th September 2017) - Nault, B. A.; Laughner, J. L.; Wooldridge, P. J.; Crounse, J. D.; Dibb, J.; Diskin, G.; Peischl, J.; Podolske, J. R.; Pollack, I. B.; Ryerson, T. B.; Scheuer, E.; Wennberg, P. O.; et al.
Abstract: Lightning is one of the most important sources of upper tropospheric NO x ; however, there is a large spread in estimates of the global emission rates (2–8 Tg N yr −1 ). We combine upper tropospheric in situ observations from the Deep Convective Clouds and Chemistry (DC3) experiment and global satellite‐retrieved NO2 tropospheric column densities to constrain mean lightning NO x (LNO x ) emissions per flash. Insights from DC3 indicate that the NO x lifetime is ~3 h in the region of outflow of thunderstorms, mainly due to production of methyl peroxy nitrate and alkyl and multifunctional nitrates. The lifetime then increases farther downwind from the region of outflow. Reinterpreting previous analyses using the 3 h lifetime reduces the spread among various methods that have been used to calculate mean LNO x emissions per flash and indicates a global LNO x emission rate of ~9 Tg N yr −1, a flux larger than the high end of recent estimates. Key Points: The upper tropospheric NO x lifetime is shorter than typically assumed A shorter NO x lifetime improves agreement among various methods used to calculate mean lightning NO x emission rates per flash Global lightning NO x emission rates are estimated to be ~9 Tg N yr −1 Plain Language Summary: Lightning is an important source of upper troposphere nitrogen oxides; however, there is high uncertainty in the amount of nitrogen oxides produced from lightning. Using recent updates in upper tropospheric nitrogen oxides chemistry, this study decreases this uncertainty from a factor of 4 to less than a factor of 2 and shows that the amount of nitrogen oxides produced from lightning should be higher.